2011
DOI: 10.1093/annhyg/meq098
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Respiratory Health: What Should be the Constituents of an Effective RPE Programme?

Abstract: Although personal respiratory protection is widely recognized as having a lower priority than reduction of any risk at source, respiratory protective equipment (RPE) is a major part of risk management for many employers. We have identified the key elements of what constitutes an effective risk control programme involving RPE, through a 3-fold approach involving (i) a review of the published scientific literature, (ii) exploring the issue through >40 years of research publications from the Institute of Occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Howie pointed out the necessity of employee grounding in order to ensure the proper motivation for wearing RPE, including information of the consequences for the workers' health from exposure, the necessity of having correct equipment available, knowledge of correct use and the importance of optimal fit. Graveling et al (2011) also provided recommendations for proper RPE programs. They stated that all management levels need to understand the importance of, and need for RPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Howie pointed out the necessity of employee grounding in order to ensure the proper motivation for wearing RPE, including information of the consequences for the workers' health from exposure, the necessity of having correct equipment available, knowledge of correct use and the importance of optimal fit. Graveling et al (2011) also provided recommendations for proper RPE programs. They stated that all management levels need to understand the importance of, and need for RPE.…”
Section: Discussionmentioning
confidence: 99%
“…In a review by Graveling et al (2011), the authors suggested several measures to optimize RPE use and compliance among workers. The role of management with regards to facilitating use, providing the correct equipment and training in addition to aspects of the RPE equipment such as user comfort and technical appropriateness were pointed out.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been recommended that RPE should be used only in a systematic and documented manner as detailed in the respiratory protection program (RPP). As part of respiratory risk control in the workplace, implementing an RPP can ensure that selection, use, and care of respiratory protective equipment have been conducted correctly and expected protection has been provided to the workers [8] , [9] , [10] , [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Фактори, які впливають на правильний вибір і використання працівником ЗІЗОДскладні і неоднорідні навіть на одному робочому місці. Якщо зробити наголос на різні чинники, то це не завжди відображає те, що можна очікувати для даної галузі і даного респіратора [26][27]. Однак, розуміючи зібрану інформацію можна сказати, що до найсуттєвіших помилок при виборі фільтрувальних ЗІЗОД, наслідки якої можуть привести до фатального результату є невідповідність функціонального призначення, коли вибраний ЗІЗОД не відповідає ані типу токсикантів ані класу захист.…”
unclassified